Analiza nierówności dochodowych w państwach Unii Europejskiej - Klimczak, Piotr; Solek, Adrian (The Analysis of Income Inequalities in the EU Countries, 2009)
The main goal of the article is to analyze changes in income inequalities in the EU member countries and to answer the question if the accession process helps to increase or decrease income inequalities. The range of analysis covers the period from 1980 to 2008. The results of research show that the real convergence process requires a long time, although some symptoms of decreasing income inequalities are visible. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 138-144